2021
DOI: 10.1017/s0954422421000123
|View full text |Cite|
|
Sign up to set email alerts
|

A scoping review of chronotype and temporal patterns of eating of adults: tools used, findings, and future directions

Abstract: Circadian rhythms, metabolic processes, and dietary intake are inextricably linked. Timing of food intake is a modifiable temporal cue for the circadian system and may be influenced by numerous factors, including individual chronotype—an indicator of an individual’s circadian rhythm in relation to the light-dark cycle. This scoping review examines temporal patterns of eating across chronotypes and assesses tools that have been used to collect data on temporal patterns of eating and chronotype. A systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 107 publications
(393 reference statements)
1
12
0
Order By: Relevance
“…Chrononutrition is receiving increasing attention as an important factor to consider when developing strategies to improve cardiometabolic health in shift workers. Previous research [26] and expert consensus from the current study indicate that chrononutrition measurement needs to include not only times at which food is consumed, but also information about amount consumed (e.g., main meals versus snacks), regularity of meals, and duration and timing of the eating window. Current methods that would capture this complexity, e.g., time-stamped food diaries, are burdensome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chrononutrition is receiving increasing attention as an important factor to consider when developing strategies to improve cardiometabolic health in shift workers. Previous research [26] and expert consensus from the current study indicate that chrononutrition measurement needs to include not only times at which food is consumed, but also information about amount consumed (e.g., main meals versus snacks), regularity of meals, and duration and timing of the eating window. Current methods that would capture this complexity, e.g., time-stamped food diaries, are burdensome.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of tool development is item development, consisting of: (i) domain identification and item generation and (ii) establishing content validity [25]. Domain identification and item selection was the subject of a recent scoping review, which evaluated the impact of chronotype on temporal patterns of eating whilst simultaneously identifying and assessing the strengths and limitations of existing tools used for data collection [26]. Our scoping review found inconsistencies between studies with relation to using validated dietary tools and an inability to capture all aspects of temporal meal patterns and its relation to chronotype [26].…”
Section: Development Of a Chrononutrition Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, chronotypes in relation to the timing of eating and cardiometabolic outcomes have only been assessed in young adults [ 130 ]. Given that a mismatch between chronotype and sleep timing can lead to circadian disruption and is a risk factor for CVD [ 6 , 131 , 132 ], this is worthy of attention. Furthermore, given that chronotypes can be an indicator of biological timing [ 129 ], an effort to use TRE to minimise circadian misalignment would need to do so relative to a person’s body clock rather than to the absolute clock time.…”
Section: Proposing a New Research Agendamentioning
confidence: 99%
“…Although it is a fairly new tool, CP-Q is a concise and thorough measurement of chrononutrition [53]. It is easily administered with little instruction, and its validity and reliability have been tested [53,54]. The questionnaire consists of 18 items (open-ended and multiple-choice options) designed to assess both chrononutrition behaviors and preferences during an average week (on typical work/school and free/weekday days).…”
Section: Chrononutritionmentioning
confidence: 99%